The Language of Civil Engineering: Corpus-based Studies on Vocational School Textbooks in Malaysia - Thiruchelvam, Sivadass; Jin, Ng Yu; Tong, Chong Seng; Ghazali, Azrul; Mat Husin, Norhayati Bte (International Journal of Engineering and Technology, 2018)
Engineering textbooks are specialized in nature, containing technical terminology which can be challenging to learners. For better comprehension of engineering concepts, there is a need for bridging the language gap by focusing on the frequently used and important engineering vocabulary. Most English Language Teaching (ELT) teachers do not necessary possess the specialist language in the field of engineering which can be rather confusing to them. It has been reported that Malaysian engineering textbooks (syllabus) were not written based on any word lists or corpora. Hence, learners require the language needed in the field of engineering â€“ English for Engineering Purposes (EEP). To meet this requirement, specialised engineering textbooks were studied to specify the meaningful lexical components which can facilitate learners to assimilate into their discourse community. In the field of civil engineering, there is no exception that learners too need to understand the composition of words found in their textbooks. This study shows the exact word lists and suggests what learners and teachers can do to learn the â€œlanguage of civil engineeringâ€.